Performance of Single Degree of Freedom (SDOF) Systems Subjected to The Near-Fault Earthquakes - Mhawish, Ayah Hameed; Reisn, Hussam K. (Al-Nahrain Journal for Engineering Sciences, 2024)
This paper aims to assess the structures’ seismic response with a system of Single-degree-of-freedom exposed to near-fault earthquakes, taking into account the effect of pulse period, shear wave velocity (VS30), and fault mechanism. Strong ground motion data were taken for different events in different places around the world and the prism software program is used for the analysis of seismic response for structures recognized as single-degree-of-freedom systems. Results show that the ground motion with a higher value of (VS30) provides an acceleration response higher than that of the lower value of (VS30). However, the findings revealed that the peak displacement requirements are observed in a nearby of the pulse period limits. In addition, it is noticed that there is an obvious increase in spectrum demand with longer pulse periods. Finally, results show at short vibration periods (T? 0.6sec) for both types (strike slip and dip slip) comparable results while an increment is observed in the results of the strike-slip for vibration periods more than (0.6sec) of the acceleration response spectrum. Nonetheless, for the velocity response spectrum dip-slip continuous in flocculating with a significant increase.